Challenges for the Therapeutic use of Pluripotent Stem Derived Cells - Forsberg, Magda; Hovatta, Outi (Frontiers in Physiology, 2012)
Human embryonic stem cells (hESC) and induced pluripotent stem cells (hiPSC) are an attractive cell source for regenerative medicine. These cells can be expanded to vast numbers and can be differentiated to many desired pluripotent stem cells (PSC) derived therapeutic cells. Cell replacement bears promises, but also challenges. The introduction of exogenous cells in a recipient must address several different topics; its safety, the exclusion of tumor formation, the immunological response and possible rejection, the cells cleanliness and their biological quality, and quantity representing the functionality of the PSC derived therapeutic cells. Tumor formation requires the removal of any PSC remaining after differentiation. Immunological rejection can be addressed with immunomodulation of the cells and the recipient. Cleanliness can be optimized using good manufacturing practice quality systems. At last, the functionality of the cells must be tested in in vitro and in animal models. After addressing these challenges, precise strategies are developed to monitor the status of the cells at different times and in case of undesired results, corresponding counteracting strategies must exist before any clinical attempt.